2001
DOI: 10.1073/pnas.171579898
|View full text |Cite
|
Sign up to set email alerts
|

Type I topoisomerase activity is required for proper chromosomal segregation in Escherichia coli

Abstract: Type I DNA topoisomerases are ubiquitous enzymes involved in many aspects of DNA metabolism. Escherichia coli possesses two type I topoisomerase activities, DNA topoisomerase I (Topo I) and III (Topo III). The gene encoding Topo III (topB) can be deleted without affecting cell viability. Cells possessing a deletion of the gene encoding Topo I (topA) are only viable in the presence of an additional compensatory mutation. In the presence of compensatory mutations, Topo I deletion strains grow normally; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 34 publications
4
82
0
Order By: Relevance
“…Topoisomerase I is efficient at relaxing negatively supercoiled DNA, whereas topoisomerase III is an efficient decatenating enzyme (DiGate and Marians, 1988;Champoux, 2001;Nurse et al ., 2003). E. coli cells that lack both type IA topoisomerase activities filament extensively and do not segregate chromosomal DNA properly (Zhu et al ., 2001). Deletion of the recA gene suppresses this phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topoisomerase I is efficient at relaxing negatively supercoiled DNA, whereas topoisomerase III is an efficient decatenating enzyme (DiGate and Marians, 1988;Champoux, 2001;Nurse et al ., 2003). E. coli cells that lack both type IA topoisomerase activities filament extensively and do not segregate chromosomal DNA properly (Zhu et al ., 2001). Deletion of the recA gene suppresses this phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…These results have led to the suggestion that the type IA enzymes are involved in RecA-mediated recombination and that they may specifically remove recombination intermediates before chromosome segregation (Zhu et al ., 2001;Wang, 2002). Furthermore, yeast Sgs1 and human BLM helicases, members of the RecQ family, have been shown to interact with Topo III (Gangloff et al ., 1994;1999;Haber, 1999;Bennett et al ., 2000;Shimamoto et al ., 2000;Wu et al ., 2000;Fricke et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This omnipresence of the type IA enzymes suggests that they play an essential role in processing intracellular DNA, and genetic studies of microorganisms have provided strong support of this idea. Escherichia coli lacking both of the type IA DNA topoisomerases, for example, is not viable (4). Similarly, yeast top3 mutants lacking DNA topoisomerase III (Top3), the only type IA enzyme in yeasts, exhibit a complex phenotype including slow growth, hypersensitivity to DNA-damaging agents, genome instability, and low viability (5-7).…”
mentioning
confidence: 99%
“…Whereas sporulation of Saccharomyces cerevisiae top3 diploids yields no viable spores, this lethality can be prevented by blocking meiotic recombination (7). Concordantly, inactivation of the E. coli recA gene, which is essential for homologous recombination, restores viability of a topA topB double mutant lacking both DNA topoisomerases I and III (4). Earlier studies also showed that the defects of mitotic yeast top3 cells could largely be suppressed by mutations in a helicase of the RecQ family, the Sgs1 protein in S. cerevisiae and the Rqh1 protein in Schizosaccharomyces pombe (6,8,9).…”
mentioning
confidence: 99%
“…The complexity of DNA topoisomerase II, with two dissimilar polypeptides each with multiple domains having different enzymic activities, seems too great to have preceded topoisomerase I. The fact that DNA topoisomerase I is essential for bacterial DNA seqregation (Zhu et al, 2001) is consistent with an early origin.…”
Section: Origin Of the Basic Machinery For General Recombinationmentioning
confidence: 99%